EDUCATIONAL COOPERATION: JAPAN AND THE REPUBLIC OF VIETNAM IN THE 1960S-1970S - Thuy Dung, Truong (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
The twentieth century gave rise to a unique context and significantly altered the world order and the position of states in international relations. The regional and world wars occurred consecutively, creating a bias in research reflected in the last decade's publications, where mainstream research has focused on issues of war and conflict. Undeniably, those wars had decisively shifted the fate of many countries; it would be flawed if studies only focused on war issues and underestimated non-military issues. For example, in the circumstances of the twentieth-century conflicts, particularly in the context of the Cold War, Japan and the Republic of Vietnam maintained a special relationship, not just a military alliance, but laid the first foundations for becoming cooperative partners in developing a modern education. The studies on educational cooperation between the two countries in this period are limited, lacking systematic research on this issue. Hence, this research paper not only helps to fill the gap in the educational cooperation relationship between Vietnam and Japan in the 1960s and 1970s, but more importantly, it will help to clarify a historical lineage of educational collaboration. Although it is not the main thread of the twentieth century, it has a lasting impact on the long-term development of the two countries and shows the trend of cooperation in the post-Cold War modern era.